Major depressive disorder, functional and physical performances of Malaysian brain tumour patients - Naing, N.N.; Das, P.; Wan-Arfah, N.; Kon, N.; Kueh, Y.C.; Rasalingam, K. (2018)
Brain tumour diagnosis affects the lives of many patients, and the burden can be overwhelming for patients with psychiatric disorders. The study aimed to determine the prevalence of major depressive disorder (MDD) and its severity among Malaysian brain disorder patients. The study also investigated on changes in functional and physical performance of patients and its relationship with macrophages inflammatory cells. This study was conducted at Hospital Kuala Lumpur (n=100) and Hospital Universiti Sains Malaysia (n=22). International Neuropsychiatric Interview MINI questionnaire, Patient Health Questionnaire PHQ-9, Karnofsky performance scale (KPS) and Barthel Index (BI) questionnaire were used in the study. The plasma CD68 macrophages measured by commercialized Elisa kit. Spearman rho correlation was used to examine the relationship among the variables. The prevalence of MDD among brain tumour or brain disorder patients was 30.0% (n=30) and severe depression was 6.67% %. The KPS score of the astrocytic glioma patients reduced aer surgery and improved at the 6th month of post-surgery. The BI score was improved aer the surgery. The KPS score correlated with BI score. However no significant correlation was found with CD68 macrophage level. Thus targeting these parameters might play an important role in the effective treatment of the patients.